2021
DOI: 10.3390/molecules26196046
|View full text |Cite
|
Sign up to set email alerts
|

Cyclodextrin Polymers as Delivery Systems for Targeted Anti-Cancer Chemotherapy

Abstract: In the few last years, nanosystems have emerged as a potential therapeutic approach to improve the efficacy and selectivity of many drugs. Cyclodextrins (CyDs) and their nanoparticles have been widely investigated as drug delivery systems. The covalent functionalization of CyD polymer nanoparticles with targeting molecules can improve the therapeutic potential of this family of nanosystems. In this study, we investigated cross-linked γ- and β-cyclodextrin polymers as carriers for doxorubicin (ox) and oxaliplat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 51 publications
1
9
0
Order By: Relevance
“…The CE and K 11 values are in the same range as those obtained for other β-CyD systems [ 24 , 25 , 58 ].…”
Section: Resultssupporting
confidence: 73%
See 1 more Smart Citation
“…The CE and K 11 values are in the same range as those obtained for other β-CyD systems [ 24 , 25 , 58 ].…”
Section: Resultssupporting
confidence: 73%
“…Great interest is focused on the CyD-based polymers that can form water-soluble and stable NPs [ 19 ]. Furthermore, CyD-based NPs have been functionalized with vitamins, sugars, and peptides to actively target cancer cells and increase tumor internalization [ 15 , 20 , 21 , 22 , 23 , 24 , 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…The cross-linked β-CD and γ-CD polymers exhibited multiple cavities of different sizes, such that two drugs of different sizes could be transported. Bognanni et al reported preparation of cross-linked β-CD and γ-CD polymers through epichlorohydrin, wherein targeted modification of the surface of CD enabled targeting function 38 . This cross-linked polymer could assemble DOX and oxaliplatin at the same time.…”
Section: Co-transport Of Different Drug Combinationsmentioning
confidence: 99%
“…21 In recent years, CyD multi-cavity systems have also been studied to improve drug inclusion. [22][23][24][25] CyD dimers have also been synthesized with linkers with different lengths and rigidity. [26][27][28][29][30][31][32] The length, flexibility, and structure of the linker connecting the two CyDs may considerably affect the thermodynamic parameters of inclusion phenomena and determine the host-guest binding modes.…”
Section: Introductionmentioning
confidence: 99%